Extraction Technologies Of High Viscosity Oil And Natural Bitumen Deposits (Texas Journal of Engineering and Technology, 2022)
The article presents methods of extraction of high-viscosity oil deposits, as well as natural bitumen deposits. It should be noted that bitumen mining methods are different from viscous oil mining, but in some cases the methods can be used in several fields. The choice of methods is primarily influenced by the geological-physical properties of oil-gas reservoirs and the physical properties of oil-saturated fluids.